Strategi Alternatif Pembangunan Manusia Melalui Parawisata Halal di Indonesia Pasca Covid-19 - Ihsan, Akmal; Kusuma, Alan Budi; Hatbah, Muhammad As’ad (Jurnal Magister Ekonomi Syariah, 2022)
Halal tourism in Indonesia is the largest tourism in the world that presents a lot of natural beauty, culture, and comfortable places of worship. In the economic field, halal tourism contributes significantly to state income, which is around 10.4% and employment of around 313 million people. This proves that halal tourism in Indonesia has a positive effect on national income and increases human development. But that was all achieved before the Covid-19 outbreak hit Indonesia. During the pandemic, halal tourism objects experienced a drastic decline. Many halal tourism sub-sectors such as airlines, lodging, and places to eat are feeling the impact. For this reason, an alternative and complex strategy concept is needed to restore the existence of halal parawista in Indonesia. The right method to respond to the author's goal is a qualitative descriptive method with the help of a SWOT analysis consisting of strengths, weaknesses, opportunities, and threats. The results obtained in this article are: first, the strength of Indonesian halal tourists is quite large because it has many beautiful natural destinations, easy access to tourist attractions, the availability of many places of worship, lodging and eating places that have been tested for halalness, and the friendliness of the Indonesian population. in welcoming incoming tourists; Secondly, from the side of weakness, health protocols are considered too strict, such as mandatory vaccines, wearing masks, maintaining distance, and the like, thereby reducing tourist intentions. Another weakness is the lack of human resources in managing halal tourism, as well as the lack of government facilities in assisting small and medium enterprises in marketing their products; the third is seen from the opportunities that can be utilized by the government, namely focusing on the six basic needs of Muslim tourists, namely maintaining halal food, prayer facilities, Ramadan services, water-friendly bathrooms, no non-halal activities, and improving recreational facilities; Fourth, in terms of threats, the government needs to pay attention to competition with neighboring countries, focus on halal certification, and also the spike in Covid-19 cases. The analysis above is believed to be an alternative strategy in increasing halal tourism in Indonesia so that it makes a major contribution to the country, especially in its human development.